Methodological aspects of project management in the creative industry - Pavlikha, Nataliia; Bilous, Oleksandr (Вежа-Друк, 2023)
Before the war, Ukraine had a strong creative industry, including IT, architecture, engineering, information services, television, advertising, and marketing. These activities, based on intelligence, knowledge, creativity, innovation, and the creation of unique products, have high added value. The creative industry provides an opportunity to create new creative and innovative solutions to preserve the presentation of historical and cultural heritage. For example, video tours, short films, or mobile applications can be created to demonstrate the uniqueness and beauty of cultural monuments and provide useful information about their history and significance. Project management in the creative industries in a time of change and challenge is essential to success. The pace of change in this industry requires flexibility and quick response to new ideas and trends. The complexity of projects in the creative industries requires organizing the work of teams, еfficiently allocating resources, and monitoring the implementation of tasks. The competitive environment forces creative companies to quickly introduce new products and innovations. The challenges of change require adaptability and flexibility in project planning and execution. Considering these aspects, effective project management becomes a key factor for success in the creative industry .
Keywords: creative industry; project management; methodological aspects of project management; creative projects; 502.333